2021
DOI: 10.1182/bloodadvances.2020002517
|View full text |Cite
|
Sign up to set email alerts
|

Challenging conventional karyotyping by next-generation karyotyping in 281 intensively treated patients with AML

Abstract: Although copy number alterations (CNAs) and translocations constitute the backbone of the diagnosis and prognostication of acute myeloid leukemia (AML), techniques used for their assessment in routine diagnostics have not been reconsidered for decades. We used a combination of 2 next-generation sequencing–based techniques to challenge the currently recommended conventional cytogenetic analysis (CCA), comparing the approaches in a series of 281 intensively treated patients with AML. Shallow whole-genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…To date, the next-generation sequencing (NGS)-based methods such as whole genome sequencing (WGS) [34,35], whole transcriptome sequencing (WTS) [36][37][38], and targeted RNA sequencing (RNA-Seq) [39][40][41], with the enormous power of precise detection of all known and even novel translocations and/or fusions simultaneously, have been implemented as a diagnostic tool for hematologic malignancies including inv(16)/t(16;16) AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the next-generation sequencing (NGS)-based methods such as whole genome sequencing (WGS) [34,35], whole transcriptome sequencing (WTS) [36][37][38], and targeted RNA sequencing (RNA-Seq) [39][40][41], with the enormous power of precise detection of all known and even novel translocations and/or fusions simultaneously, have been implemented as a diagnostic tool for hematologic malignancies including inv(16)/t(16;16) AML.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FISH assays including CBFB FISH have been applied either as a tool for the confirmation of novel fusions and/or copy number variants (CNVs) or solving the discrepancies between these new methods and karyotype analysis in these reports [34,35,37]. Although implementation of these NGS-based methods in clinical diagnosis of myeloid neoplasia is still at a stage of development and validation in our institute and none of the cases in this cohort was tested with any of these new methods yet, however, based on the biology of these methods and the parameters used in the published reports, we can postulate the results, as summarized in Table 5, of these methods were applied to all 271 cases with CBFB rearrangement in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, six gene fusions not reported in the cytogenetic data were detected by WGS in NK-AML. This highlights the relevance of genomic sequencing to be implemented as clinical cytogenomic analyses as recently suggested [ 27 , 28 ]. Certain cryptic cytogenetic events of prognostic importance are difficult to capture in routine cytogenetic examinations, including, for instance, inv(16)(p13q24) ( CBFA2T3 - GLIS2 ) [ 29 ] and rearrangements involving 11p15 ( NUP98 fusions) [ 10 ].…”
Section: Discussionmentioning
confidence: 71%
“…Certain cryptic cytogenetic events of prognostic importance are difficult to capture in routine cytogenetic examinations, including, for instance, inv(16)(p13q24) ( CBFA2T3 - GLIS2 ) [ 29 ] and rearrangements involving 11p15 ( NUP98 fusions) [ 10 ]. For these cryptic events, WGS or transcriptome (RNA) sequencing may have a higher diagnostic yield detecting gene fusions or their expressed fusion transcripts, respectively [ 27 , 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a head-to-head comparison of WGS (tumor-only, 60×) analysis to conventional cytogenetics and targeted sequencing not only confirmed accurate genomic profiling by WGS but also showed that WGS identified additional clinically relevant events in 17% (40/235) of patients and reclassified risk group assignments in 16% (19/117) of patients ( 13 ). Shallow WGS and WTS also demonstrated greater sensitivity in CNA detection and fusion detection in AML patients, respectively, compared with conventional cytogenetic analysis ( 19 ); concordance was high between cytogenetic analysis and shallow WGS (approximately 96%) or WTS (approximately 99%). Likewise, clinical value of WGS/WGTS in routine care of patients with solid tumors has been shown or is being investigated; e.g., the Hartwig Medical Foundation ( 20 ), the MASTER ( 21 ), and the WIDE ( 22 ) studies.…”
Section: Discussionmentioning
confidence: 89%